An institutional perspective and the role of the state for Chinese OFDI - Ren, Bing; Liang, Hao (Henry Stewart Talks, 2013)
State capitalism, State-owned enterprises, National champions, Formal control to informal control, Corporate governance and administrative system, Managerial incentive structure, Ideological control, Political promotion system, Enforcement mechanism, Two-stage globalization, Split-share reform, The role of the Chinese state, The role of the foreign country state, Debates